2017
DOI: 10.3892/mmr.2017.6973
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38MAPK potentiates mesenchymal stem cell therapy against myocardial infarction injury in rats

Abstract: The present study aimed to investigate the protective effect of mesenchymal stem cell (MSC) therapy in combination with p38 mitogen‑activated protein (MAPK) inhibition against myocardial infarction (MI) injury in rats, and to elucidate the underlying mechanisms. An MI model was established by ligation of the anterior descending branch of the left coronary artery. The rats were divided into four groups: MSC transplantation, p38MAPK inhibitor (SB203580), MSC + SB203580 and model control group. HE staining and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It was earlier confirmed by few authors that certain specific amino acid domain (asparagine, glycine, glutamine, and alanine) of collagen interact with α 2 β 1 integrin on the bone marrow mesenchymal stem cell membrane and can lead to up-regulate bone matrix synthesis through activation of Runx2 signaling pathway [29,36,41,49,50]. Kawaguchi et al [51] observed the presence of radioactive dipeptides [14C] Pro-Hyp in osteoblasts, osteoclasts, dermal fibroblasts, epidermal cells, synovial cells, and chondrocytes after 24 h of oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…It was earlier confirmed by few authors that certain specific amino acid domain (asparagine, glycine, glutamine, and alanine) of collagen interact with α 2 β 1 integrin on the bone marrow mesenchymal stem cell membrane and can lead to up-regulate bone matrix synthesis through activation of Runx2 signaling pathway [29,36,41,49,50]. Kawaguchi et al [51] observed the presence of radioactive dipeptides [14C] Pro-Hyp in osteoblasts, osteoclasts, dermal fibroblasts, epidermal cells, synovial cells, and chondrocytes after 24 h of oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p38 elicits protective effects during ischemic conditions ( Nakano et al, 2000 ; Fujimoto et al, 2004 ; Hsu et al, 2007 ) and plays an important role in the activation of brown adipose tissue ( Leiva et al, 2020 ). However, activation of p38 has been linked to inflammatory cytokine production ( Li et al, 2005 ) and ASC aging ( Zhang et al, 2020 ), and its inhibition potentiates ASC and EV therapy ( Zhang et al, 2017 ; Chen et al, 2020 ). Our in vitro studies revealed that treatment of uninjured HK2 cells with EVs increased expression of p-p38, underscoring the potential of EVs to activate members of MAPK signaling in recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other reports to improve the complex microenvironment in heart diseases have been published. Myocardial transfection of HIF-1α via an adenoviral vector or injection of p38MAPK inhibitor (SB203580) was used to optimize to effects of transplanted MSCs 76,77 . The impact of heart disease environment on the transplanted MSCs and the approach to improve to transplantation-site microenvironment are worth exploring in the future.…”
Section: Problems and Prospectsmentioning
confidence: 99%